Bibliometric analysis of global research on dialectical behavior therapy from 1987 to 2024 - Shi, Kuo; Zhang, Li-Yi; Gao, Bing-Ling; Qian, Ying; Huang, Xue-Bing; Yue, Jing-Li (Frontiers in Psychology, 2025)
ObjectiveThis study explores researches of dialectical behavior therapy (DBT) in mental health to provide an overview of current knowledge landscape and predict future development trends of DBT.MethodThe bibliometric approach was used in the study. Articles on DBT-related research were retrieved from the Web of Science Core Collection (WoSCC) database up to December 31, 2024, and analyzed using VOSviewer and CiteSpace.ResultsA total of 2,723 articles were analyzed. DBT research has grown significantly since the 1990s, with the United States leading in publication volume, citation impact, and academic collaboration. Research is primarily conducted in developed countries like the United States, the United Kingdom, and Germany, with limited contributions from emerging economies. Cognitive and Behavioral Practice is the most prolific journal in DBT research. Key topics include borderline personality disorder (BPD), suicide, adolescent interventions, forensic psychiatry, and family therapy. Recently, keywords such as “emotion dysregulation” and “mobile phone” have become research hotspots.ConclusionDBT research has evolved from early focus areas like BPD and suicide to studies on emotion dysregulation mechanisms and digital interventions. While the United States dominates the field, expanding participation from emerging countries and strengthening global collaboration could advance DBT research and improve mental health accessibility. This bibliometric analysis provides a global perspective and long-term trend insights, highlighting future directions in neurobiological mechanisms, methodological innovation, and technological integration.